2006
DOI: 10.1182/blood-2006-02-005702
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 clinical results with tandutinib (MLN518), a novel FLT3 antagonist, in patients with acute myelogenous leukemia or high-risk myelodysplastic syndrome: safety, pharmacokinetics, and pharmacodynamics

Abstract: Tandutinib (MLN518/CT53518

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(166 citation statements)
references
References 24 publications
(43 reference statements)
3
162
0
Order By: Relevance
“…Expression of Mcl-1 is upregulated at the transcriptional level by STAT5, PI3K/Akt and Mek/Erk pathways [11][12][13] and at the posttranslational level by the PI3K/ Akt pathway. 14 It has been reported that FLT3 inhibition induces apoptosis in leukemic blasts of AML patients who carry the FLT3 mutation, [15][16][17][18][19][20][21] though the mechanism remains unknown. Several FLT3 inhibitors have been developed, including sorafenib (BAY43-9006), lestaurtinib (CEP-701), PKC412, sunitinib (SU11248) and tandutinib (MLN-518), but clinical trials using these inhibitors as single agents have not been successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Mcl-1 is upregulated at the transcriptional level by STAT5, PI3K/Akt and Mek/Erk pathways [11][12][13] and at the posttranslational level by the PI3K/ Akt pathway. 14 It has been reported that FLT3 inhibition induces apoptosis in leukemic blasts of AML patients who carry the FLT3 mutation, [15][16][17][18][19][20][21] though the mechanism remains unknown. Several FLT3 inhibitors have been developed, including sorafenib (BAY43-9006), lestaurtinib (CEP-701), PKC412, sunitinib (SU11248) and tandutinib (MLN-518), but clinical trials using these inhibitors as single agents have not been successful.…”
Section: Introductionmentioning
confidence: 99%
“…Several FLT3 inhibitors have been developed, including sorafenib (BAY43-9006), lestaurtinib (CEP-701), PKC412, sunitinib (SU11248) and tandutinib (MLN-518), but clinical trials using these inhibitors as single agents have not been successful. [17][18][19][20][21] Conventional chemotherapy in combination with FLT3 inhibitors has therefore emerged as the preferred therapeutic strategy in the current phase 3 trials. [17][18][19] It is conceivable that targeting multiple arms of the apoptotic regulatory machinery with FLT3 inhibition would be more efficacious than targeting the mutated FLT3 alone.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Other FLT3 inhibitors showed similar limited efficacy in clinical trials. [20][21][22][23][24] The common strategy for solving this problem is to combine PKC412 with other antileukemic agents. However, to our knowledge, no data have been reported for the cytotoxic interactions of PKC412 with other agents.…”
Section: Introductionmentioning
confidence: 99%
“…A phase 2 study in relapsed/refractory patients with FLT3-ITD AML is currently recruiting patients, with interim data supporting doses of quizartinib 135 and 90 mg in men and women, respectively, due to QTc prolongation at a starting dose of 200 mg. 74 Tandutinib (MLN518) Tandutinib is more selective for FLT3 than midostaurin or lestaurtinib, although it does have some activity against plateletderived growth factor receptor-b and c-KIT. 75 Although tandutinib demonstrated some antileukemic activity as a single agent and in combination with chemotherapy in phase 1 studies, 76,77 doselimiting muscle weakness (reversible) and high rates of nausea and vomiting were observed. This may be related to the slow clearance and resultant high plasma levels of the drug.…”
Section: Quizartinib (Ac220)mentioning
confidence: 99%